COMMUNICATIVE COMPETENCE - Walean, Hanny A (JIU (Jurnal Ilmiah Unklab); Volume 7 No. 1, 2004 JIU UNKLAB, 2004)
In the field of second language teaching and learning communicative competence has gained wide insert over the years. Communicative competence refers to both knowledge and skill when interacting in actual communication. Knowledge refers to what one knows consciously and unconsciously about the language and about other aspects of communicative language use. Skill refers to how well one can perform this knowledge in actual communication. Communicative includes four areas of knowledge and skill: grammatical competence, sociolinguistic competence, discourse competence, and strategic competence.